KARAKTERISTIK HASIL UJI BAKTERI TAHAN ASAM (BTA) PADA PASIEN YANG DICURIGAI MENDERITA TUBERKULOSIS (TB) DI RSU SURYA HUSADHA TAHUN 2013 - Intan Astariani; I Wayan Putu Sutirta Yasa; A.A. Wiradewi Lestari (E-Jurnal Medika Udayana, 2015)
CHARACTERISTIC OF TEST RESULT OF ACID-FAST BACILLUS (AFB) SMEAR AMONG PATIENTS WHOSUSPECT WITH TUBERCULOSIS IN SURYA HUSADHA HOSPITAL 2013Lung Tuberculosis is a chronic infectious disease caused by Mycobacterium tuberculosis and still become the world problem until today. Indonesia placed the fifth rank as the country with tuberculosis and the prevalence was 285 cases in 100.000 people with the mortality rate 27 death in 100.000 people. To reduce the cases of tuberculosis, the best prevention and appropriate treatment become very important. The diagnosis of tuberculosis must define precisely, so it needs an accurate diagnostic method.Acid-fast bacillus (AFB) smeartest become the primary method to define tuberculosis diagnostic in developing country, but it has limitation in specificity and sensitivity. The aim of this research is to know the prevalence of test result of AFB smear among patients who suspect with tuberculosis in Surya Husadha Hospital 2013 and the characteristic of the patients. This research using cross sectional non-experimental method with secondary data from Laboratory of Surya Husadha Hospital. The sample was all the test result of acid-fast bacillus smear among patients who were tested in the Laboratory in 2013. Total of sample was 287. The result of this research was from 287 patients who had acid-fast bacillus smear in Laboratory of Surya Husadha Hospital in 2013, the patients who collected their sputum completely was 257 patients (89.55%) and non-completely sputum was 30 patients (10.45%). From the complete sputum, the positive result which is shows the prevalence of suspect tuberculosis was 31 patients (12.06%), negative result was 219 patients (81.21%), and the sample who needed retest was 7 patients (2.72%).